PENGUATAN SEKTOR-SUBSEKTOR EKONOMI DALAM UPAYA PENINGKATAN PEMBANGUNAN EKONOMI DAERAH - Wahyudi, Setyo Tri (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2008)
This research aims at identifying the potentials of economic sectors andproblems related in district Jember in East Java, for designing thedevelopment strategy. Based on purposive sampling and qualitativeapproach, this research found that the agriculture and marine sectors areof the potentials which need to develop much.Keywords: economic potentials sectors, qualitative approach